Effects of prickly structures on burrow desertion by rodents - Singla, Neena; Parshad, V R (The Indian Journal of Agricultural Sciences, 2005)
The experiment was conducted during 2002 to find out the effects of locally available prickly materials, glass dust, spiny twigs of Acacia spp and dry thorny fruits of Xanthium spp on burrow desertion by rodents [Tatera indica Hardwicke and Millardia (Rattus) meltada Gray] in fields of wheat (Triticum aestivum L. emend. Fiori & Paol.). Plugging of burrow openings twice at 15 days interval with spiny twigs of Acacia spp in block II resulted in 39.3% reduction in liveburrow density or burrow desertion which was significantly (P = 0.05) more than burrow dusting with glass dust ( 17.9%) in block I and non-significantly more than burrow plugging with fruits of Xanthium spp (23.9%) in block III. No such reduction occurred in the control fields. New burrow-digging activity sites were maximum (5.00± 0.58) and were significantly (P = 0.05) more in reference fields than in treated fields confirming burrow or field desertion by occupants in treated fields.